Analysis of vegetation indices from LANDSAT/TM and SPOT/XS data - Moreira, Maurício Alves; Nitzsche, Regina Pillis (Pesquisa Agropecuaria Brasileira, 1991)
The objective of this work was to evaluate vegetation indices (Simple Ratio, Normalized Difference and Transformed Vegetation Index) obtained on soybean and corn crops, from LANDSAT/TM and SPOT/XS data (acquired on Feb. 01, 1989). The study area is located in the southeast of Distrito Federal - Brazil. The vegetation indices were obtained from averaged values of digital numbers from 20 units (3.6 ha each one) sampled on the studied crops. The results were analysed through correlation method for equal indices but come from different sensor systems. According this research it was concluded that: the same vegetation indices were highly correlated both for soybean and corn crops and both for LANDSAT/TM and SPOT/XS; and, the lowest observed correlation (0.72) was over the soybean crop for the Transformed Vegetation Index.
Keywords: remote sensing; soybean and corn crops